Artificial Intelligence and Big Data in Medicine: A Nepali Medical Institute Perspective - Sharma, Mohan Raj (Journal of Institute of Medicine Nepal, 2025)
The integration of big data and artificial intelligence (AI) has been changing the three facets of medicine namely, medical care, medical education and research especially in the last 10 years. By offering the modeling and rapid diagnostic and evaluating facilities and offering personalized approaches they have been reshaping the medical care. These technologies strengthen biomedical research by providing better predictive modelling and optimizing clinical trials. This, in turn, helps in the evidence-based approach to medicine. Similarly, they have the potential to transform medical education as to how the course is designed, how the contents are delivered, and how we assess the competency of the trainees. However, a major concern is the responsible use of these technologies and data privacy. This article briefly discusses the application of these technologies and guidelines regarding their responsible use.